FISH SAUCE FERMENTATION OF SKIPJACK FISH (Katsuwonus pelamis L.) AT VARIOUS INCUBATION TIMES AND CONCENTRATIONS OF CRUDE PAPAIN ENZYME - Wiyati, Retno; Ariyanti, Nur Aeni (Department of Biology Education FMIPA Universitas Negeri Yogyakarta in collaboration with Perhimpunan Biologi Indonesia, 2024)
This study aims to determine the differences in variations of crude papain enzyme concentration and optimal fermentation time on the microbiological quality of skipjack tuna (Katsuwonus pelamis L.) fish sauce. This research is an experimental study with two variables: 2 different enzyme concentrations (5% and 10%) and 3 different periods (3, 7 and 11 days). The microbiological tests include the Escherichia coli contamination test, total microbial test, and total lactic acid bacteria test. Physical tests include water content tests, pH tests, and organoleptic tests. The results showed that the enzyme concentration and fermentation time affected the microbiological quality of skipjack tuna sauce. The sample with an enzyme concentration of 10% and a fermentation time of 11 days was the best sample of skipjack tuna fish sauce because no E. coli bacteria were found (negative), the total BAL test result was 8.2 x 103 cfu/mL, and the TPC result was 7.1 x 103 cfu/mL which meets SNI standards for Fish Sauce No. 01-4271-1996. This sample also had the best organoleptic test results: a non-fishy aroma, savory taste, and dark brown color. Based on the pH test, samples with enzyme concentrations of 5% and 10% and a fermentation time of 3 days have a pH value that meets the requirements, namely 5.88 (pH requirement 5-6). The results of the water content test showed that all samples did not meet the standards.